The Protective Role of Urtica dioica Seed Extract Against Azoxymethane-Induced Colon Carcinogenesis in Rats. (2nd January 2022) - Uyar, Ahmet; Doğan, Abdulahad; Yaman, Turan; Keleş, Ömer Faruk; Yener, Zabit; Çelik, İsmail; Alkan, Elif Ebru
Abstract: The aim of this study was to investigate the protective role of Urtica dioica seed (UDS) extract against azoxymethane (AOM)-induced colon carcinogenesis in rats. Thirty-two male Wistar albino rats were divided into four groups: Control, AOM, AOM + UDS, and UDS. The AOM and AOM + UDS groups were induced by AOM (15 mg/kg body weight) subcutaneously once a week for 10 weeks. AOM + UDS and UDS groups additionally received fed with pellets included 30 ml/kg UDS extract. At the end of the trial, blood and colon tissue samples were taken from the rats following necropsy. The gross and histopathological findings revealed that the administration of UDS extract significantly decreased lesions including aberrant cript foci, adenoma, and adenocarcinoma formation both numerically and dimensionally. Immunohistochemically, slight CEA and COX-2, strong Caspase-3 immune-expressions were detected in the group AOM + UDS compared to AOM group. Biochemical examinations indicated that a markedly increase in the malondialdehyde and fluctuated antioxidant defense system constituents levels such as reduced glutathione, glutathione s -transferase, glutathione peroxidase, superoxide dismutase were restored in AOM + UDS group. These results reveal that the UDS may act as a chemopreventive dietary agent, inducing apoptosis, resulting in a significant reduction of colon carcinogenesis.